HUBUNGAN TINGKAT KEBISINGAN DENGAN TEKANAN DARAH PENDUDUK DI SEKITAR BANDAR UDARA HALIM PERDANAKUSUMA TAHUN 2023 - Neva Azzahra, (2023)
By 2021, there were 252,553 people with hypertension in East Jakarta. One of the major causes of hypertension is noise. The study aims to look at the relationship between noise and blood pressure of the population living around Halim Perdanakusuma Airport. The research was conducted in May 2023 using analytical observational methods with a cross-sectional research design. The total sample was 86 respondents using random walking sampling technique. The measuring instruments used are a sound level meter and a digital tensimeter. The questionnaires used in this study were IPAQ for physical activity and Recall 24 hours for fat consumption. In bivariate and multivariate analysis, the cox regression test is used. From the results of the analysis, there were 81% of respondents who had hypertension and 64% of the respondents whose homes were noisy. And from the results of the multivariate analysis between blood pressure and noise obtained a PR of 1.4 (95% CI = 0.761-2,399) which means at risk, but there were no confounding variables in this study. Thus, people living in places with noise ≥55 dB have a 1.4 times greater risk of developing hypertension than those living in places with <55dB.